Analyzing Cognitive Skill Balance in Arabic Summative Assessments: A Case Based on LOST-MOST-HOST Framework - Kabalmay, Taqiyuddin; Rahmadewi, Sintya; Alim Aziz, Anshari Nur Muhammad; Tantawi, Imam (At-tadzkir: Islamic Education Journal, 2025)
This study is motivated by the absence of item analysis based on Anderson and Krathwohl’s cognitive taxonomy in the implementation of summative assessment, indicating a gap in the evaluation practices of Arabic language instruction in Grade VIII at MTsN Ambon. Item analysis is essential to ensure that assessment instruments accurately measure students’ cognitive abilities in alignment with the learning objectives set out in the curriculum. This study aims to analyze the level of difficulty of the year-end summative test items in the Arabic language based on the revised taxonomy of Anderson and Krathwohl, which includes six cognitive levels: remembering, understanding, applying, analyzing, evaluating, and creating. This research employs a descriptive qualitative approach using non-interactive methods such as documentation, interviews, and observation. The research subjects are Arabic language test papers used in the year-end summative assessment for Grade VIII at MTsN Ambon in the 2022/2023 academic year. The findings reveal that most items fall within the MOST (moderate thinking skills) category, while LOTS (lower-order thinking skills) and HOTS (higher-order thinking skills) categories remain significantly underrepresented. This finding indicates that the assessment instruments do not yet comprehensively reflect the full spectrum of students’ cognitive domains. Therefore, this study recommends the development of more balanced assessments based on the LOTS, MOST, and HOTS framework, along with teacher training in constructing test items grounded in a comprehensive cognitive taxonomy, to enhance the validity of assessments and support more effective and meaningful learning processes.